Growth performance of carps in a hardwater seasonal pond - Athithan, S; Sanjeeviraj, G (Indian Journal of Fisheries, 2011)
Experiments were carried out to assess the growth performance of carps under extensive composite culture in a hardwaterseasonal pond, where water hardness ranged from 150 to 758 mg l-1. Carp seed (catla - Catla catla; rohu - Labeo rohita;mrigal - Cirrhinus mrigala; silver carp - Hypothalmichthys molitrix; common carp - Cyprinus carpio and grass carp -Ctenopharyngodon idella) were stocked at the rate of 1537 no. / ha. During the study period, the carp production recordedwas 1846.14 kg/ 2.7 ha/ 300 days. The performance of carps on the basis of growth and survival under hardwater conditionwas encouraging.